Vibostolimab coformulated with pembrolizumab (vibo/ pembro) plus chemotherapy (chemo) as first-line treatment for advanced esophageal cancer (ec): Results from cohort E of the phase II KEYVIBE-005 study - Hsu, C\\-H.; Dziadziuszko, R.; Gomez Abreo, D. A.; Aksoy, S.; Gil Martin, M.; Roderburg, C.; Yen, C. J.; Arican, A.; Cassier, P.; Im, S\\-A.; Kim, S\\-B.; Kudo, T.; et al. (ELSEVIER, 2024)
Gastrointestinal Cancers Congress of the European-Society-for-Medical-Oncology (ESMO), Munich, GERMANY, JUN 26-29, 2024